Conservative surgical management of in situ subungual melanoma: long-term follow-up - Mariana Catalina De Anda-Juárez; María Abril Martínez-Velasco; Verónica Fonte-Ávalos; Sonia Toussaint-Caire; Judith Domínguez-Cherit (Sociedade Brasileira de Dermatologia, 2016)
Abstract Subungual melanoma represents 20% of all melanomas in Hispanic population. Here, we report the outcome of 15 patients with in situ subungual melanoma treated with resection of the nail unit with a 5-mm margin without amputation, followed up for 55.93 ± 43.08 months. The most common complications included inclusion cysts and nail spicules. We found no evidence of local or distant recurrences at the last visit of our follow up. Functional outcome was good, with only one patient reporting persistent mild pain. These results support functional, non-amputative surgical management of in situ subungual melanomas.